RESENSI BUKU ALL WE CAN SAVE: TRUTH, COURAGE AND SOLUTIONS FOR THE CLIMATE CRISIS - Adna Debora Melapa (Universitas Kristen Satya Wacana, 2025)
Judul : All We Can Save: Truth, Courage and Solutions for The Climate Crisis Penyunting : Ayana Elizabeth Johnson & Katharine K. Wilkinson Penerbit : One World, New York Tahun : 2020 Halaman : 448 halaman ISBN : 978-0593-13877-6